THE IMPROVEMENT OF BUILDINGS AND INFRASTRUCTURE CONDITION TO ANTICIPATE DEGRADATION PROCESS OF FISH-SMOKING CENTRE IN BANDARHARJO, SEMARANG - Gagoek Hardiman (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The fish-smoking area in Bandarharjo is one of the significant industrial centers that processes fish as coastal resources. Its existence is crucial to support the characteristic of Semarang as a coastal city. The fish-smoking area, located on the bank of Semarang River, has existed since 1986. Local people keep maintaining the activities of smoking fish regardless the poor physical condition of the buildings and environmental infrastructure as a result of the high tide. In order to maintain the sustainability of fish-smoking activities, a research on the convenience of working space, physical condition of the building, and environmental infrastructure is needed.  Considering that fish-smoking industry can provide jobs for low educated people and produce alternative food for the people living in Semarang, therefore, the degrading condition of the buildings and environment in Bandarhardjo needs to be anticipated by applying the concept of space, building and environmental infrastructure quality improvement.